Application of the PRECEDE model for increasing coping behaviors against anxiety in Tehrans\' firemen - Shirin Lesan (Payesh, 2009)
Payesh2009; 8: 181-190Accepted for publication: 26 December 2007[EPub a head of print-20 Apr. 2009] Objective(s): To determine application of the PRECEDE model for increasing coping behaviors against anxiety in Tehran firemen.Methods: This was a quasi experimental study. 118 firemen (59 in experimental group and 59 in control group) from Tehran fire stations were selected as the subjects of the study through a multistage sampling. Data collection tool was a questionnaire developed by author including demographic characteristics and PRECEDE model components.Results: Comparing to the control group, after educational intervention in the study group, the mean scores of knowledge, attitude, self efficacy (predisposing factors), skill of the relaxation (enabling factor), behavior increased significantly (P<0.0001) and use of 3 educational resources (enabling factor) in area of relaxation increased significantly (P<0.03). Also, verbal persuasion and positive experiences after doing relaxation (reinforcing factors) were reported by experimental group.Conclusion: The finding of the study illustrate effective application of PRECEDE model in increasing predisposing, enabling, reinforcing factors and coping behaviors against anxiety in Tehran firemen.